Reducing Response of Structures by Using Optimum Composite Tuned Mass Dampers - Arfiadi, Yoyong (Procedia engineering, 2016)
In this paper, the optimization of composite tuned mass dampers in reducing the response of structures subject to earthquake are discussed. Composite tuned mass dampers are mass dampers that consist of two mass dampers connected in series. The mass of the auxiliary dampers is in general relatively smaller than the one of the first damper. However, in this paper the mass ratio of the auxiliary damper to total mass of dampers is varied from 0.1 up to 0.9; and the optimum stiffness and damping of the first and auxiliary dampers are obtained using real coded genetic algorithm (RCGA). From the result of optimization, it is found that the mass ratio of the auxiliary dampers does not significantly affect the response reduction of structures. It is also found that for a certain mass ratio, the resulting stiffness and damping are not unique for achieving the same performance.